Digital Bank Financial Soundness Analysis at PT Bank Jago Tbk.: CAMEL Framework Approach - Siska, Elmira (Forum Kerjasama Pendidikan Tinggi, 2023)
Out of around 250 digital banks in the world, 20% are in Asia Pacific region, and only around 5% have crossed the profitability line. Bank Jago is the sixth digital bank in Indonesia. The objective of current research is to analysis financial soundness of PT Bank Jago Tbk under CAMEL framework which includes capital, assets quality, management, earnings, and liquidity. This study employs non-statistical quantitative methods. Sampling method was utilized is purposive sample technique. The data utilized is secondary data on the financial performance of CAR, KAP, NIM, ROA, and LDR, presented as a yearly time series from 2018 to 2022. The data was taken from PT Bank Jago's yearly report, which is accessible at the bank’s web address. Data analysis was carried out by employing a horizontal analysis technique. Finding of the study conclude that Bank Jago has very strong capital, as indicated by the CAR ratio. Bank Jago's asset quality as reflected on KAP ratio is in good condition. Bank Jago's management, as indicated by the NPM ratio, Bank's profitability as indicated by the ROA ratio, and Bank’s liquidity reflected by the LDR ratio, all off still at an unhealthy level. Going forward, Bank Jago will implement a plan to boost lending by working with partners in a variety of financing goods in order to enhance financial performance.